Mimostřevní komplikace idiopatických střevních zánětů - Navrátil, Vít; Cveková, Silvia; Slodička, Peter; Aiglová, Květoslava; Pipek, Barbora; Falt, Přemysl (Vnitrni lekarstvi, 2021)
Inflammatory bowel disease (IBD) includes Crohns disease (CD) and ulcerative colitis (UC). Those are chronic gastrointestinal disorders of inflammatory nature and not fully known etiology. As a result of their immune-mediated mechanism and complex impact on the whole organism other organs than gastrointestinal system may be affected in many ways. These extraintestinal manifestations (EIM) and complications may severely deteriorate prognosis of the patient, cause his morbidity and worsen the quality of life. While classical extraintestinal manifestations, such as enteropathic arthropathy, skin or eye involvement or primary sclerosing cholangitis, share common immunopathological mechanism with IBD, whole range of other disorders may result from various anatomical or metabolic abnormalities caused by IBD or its treatment. This review focus on the most common extraintestinal complications, such as anaemia, metabolic bone disease, biliary and urolithiasis, which we meet in our daily clinical practice.
Keywords: idiopatické střevní záněty; ulcerózní kolitida; extraintestinal complications; metabolic bone disease; inflammatory bowel disease; Crohnova nemoc; anemia; Skin Diseases; lithiasis; kvalita života; Humans; Cholangitis, Sclerosing; kožní nemoci; anaemia; sklerozující cholangitida; Crohn Disease; Inflammatory Bowel Diseases; Quality of Life; Colitis, Ulcerative; lidé